(untitled) (Sebha University Conference Proceedings, 2022)
Availability and activation of the well and the level of practice and exit from the stage of raising slogans to the stage of action through the activation of laws at the public level, whether from parties of officials tainted by corruption crimes are not subject to a statute of limitations and guarantee the right to protect witnesses and whistleblowers and work on the independence of the judiciary, combating political and electoral corruption strengthening judicial and non-judicial institutions concerned with combating corruption and activating their vole by adapting local laws with the united nations convention against corruption, linking responsibility to accountability, respecting the principle of the rule of law and ensuring equality and equal opportunities for all citizens.